How come? how so? that's how things began: the inventions that changed our world - Subramanian, R P (New Delhi The Energy Resource Institute, 2014)
Inventions have changed our world beyond imagination $1 (Bfrom the simple mechanical clock to the television, telephone, computer, and microscope. Learn how it all began, where, when, and who were the pioneers in this book.s
Keywords: Invention